Retropharyngeal abscesses: a retrospective analysis of 10 patients - Karlida?, Turgut; Alpay, Hayrettin Cengiz; Kaygusuz, Irfan; Keleş, Erol; Orhan, Israfil; Karlida?, Gülden Eser; Yalçin, Sinasi (My University, 2008)
OBJECTIVES: Retropharyngeal abscess is a serious and life-threatening disease due to its anatomic location and potential to obstruct the upper airway. We evaluated the clinical characteristics, diagnosis, and treatment of patients with retropharyngeal abscesses. PATIENTS AND METHODS: The study included 10 patients (6 males, 4 females; mean age 9+/-11 years; range 4 months to 32 years) who received medical and surgical treatment with the diagnosis of retropharyngeal abscess. The patients were evaluated with respect to etiology, clinical symptoms and signs, treatment, complications, and hospital stay. RESULTS: The most frequent etiological factor was upper airway infection (70%), followed by dental abscess in two patients (20%), and soft tissue injury due to foreign body ingestion in one patient (10%). The presenting symptoms and signs included dysphagia (100%), respiratory distress (80%), limited neck motion (80%), fever (60%), and neck pain (50%). Treatment consisted of surgical drainage and parenteral antibiotic combination of cefazolin sodium and metronidazole. The mean hospital stay was 7.1+/-5.3 days. Complications were seen in two patients, being empyema and upper airway obstruction, respectively. CONCLUSION: Surgical drainage combined with early antibiotic treatment is an effective method in the management of retropharyngeal abscesses and in preventing complications.
Retrofarengeal apse: 10 olgunun geriye dönük de?erlendirilmesi.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Anti-Infective Agents; Cefazolin; Chemotherapy, Adjuvant; Child; Child, Preschool; Deglutition Disorders; Drainage; Female; Humans; Infant; Male; Metronidazole; Retroperitoneal Space; Retropharyngeal Abscess; Retrospective Studies; Young Adult; antiinfective agent; cefazolin; metronidazole; adjuvant chemotherapy; adolescent; adult; article; child; dysphagia; female; human; infant; male; pathology; preschool child; retroperitoneum; retropharyngeal abscess; retrospective study; wound drainage